Contributing to the knowledge of Brazilian Sphingidae diversity: the first record of Adhemarius daphne daphne Boisduval, 1785 and Amphimoea walkeri Boisduval, 1785 in South Brazil - Avila Jr., Rubem S. de; Moura, Jéssica P. (Entomological Communications, 2021)
Three individuals (two males and one female) of Adhemarius daphne daphne Boisduval, 1785 and an exemplar of Amphimoea walkeri Boisduval, 1785, were caught in Maquiné and Cerro Largo municipalities, respectively, indicating the first occurrence of these two taxa in the Rio Grande do Sul state, South Brazil.